Electronic Properties of MoS2/MX2/MoS2 Trilayer Heterostructures: A First Principle Study. (1st January 2016) - Datta, Kanak; Khosru, Quazi D. M.
Abstract : In this work, we have presented a first principle simulation study on the electronic properties of MoS2 /MX2 /MoS2 (M = Mo or W; X = S or Se) trilayer heterostrcuture. We have investigated the effect of stacking configuration, bi-axial compressive and tensile strain on the electronic properties of the trilayer heterostructures. In our study, it is found that, under relaxed condition all the trilayer heterostructures at different stacking configurations show semiconducting nature. The nature of the bandgap however depends on the inserted TMDC monolayer between the top and bottom MoS2 layers and their stacking configurations. Like bilayer heterostructures, trilayer structures also show semiconducting to metal transition under the application of tensile strain. With increased tensile strain the conduction band minima shifts to K point in the brillouin zone and lowering of electron effective mass at conduction band minima is observed. The study on the projected density of states reveal that, the conduction band minima is mostly contributed by the MoS2 layers and states at the valance band maxima are contributed by the middle TMDC monolayer.